A Review of Maritime English Teaching Curriculum in China - HUI, Zhang; ISHAK, Nor Asniza Binti (Journal of Research in Educational Sciences, 2022)
English for Special Purpose (ESP) is more and more popular and paid more attention nowadays. This concept paper introduces the background, definition, nature and current situation of Maritime English. Also, as to the problems in teaching and learning Maritime English, some solutions are provided to deal with the problems as well. Then, author introduces the Maritime English curriculum in China, including the philosophy to design, teaching materials, objectives, effects and so on. Lastly, evaluation comes in the end. It not only gives us a clear understanding of current Maritime English curriculum in China, but also the suggestions to improve it under Chinese context. This is very meaningful for the education of English for Special Purpose (ESP) in the future.